(3ebOeI Gdi GdGfJQfJ (B/s - (3GdbGVj, RjGO hCNQhfs ((3YeGf(B: s (3OGQ UaGA ddfTQ hGdJhRjY(B, s, 2000)
(3jbOe gPG GdcJGH TQM eHSWddGfJQfjJ eY UhQ hQSheGJ dJSdjW GdeMJhi ceG jMcj HGdJOQL Yf JWhQ GdCfJQfjJs
Keywords: (3GfJQfJs; (3THcGJ GdEJUGds; (3hjHs